Pemanfaatan Limbah Bulu Ayam Potong Sebagai Pelet Pakan Lele Untuk Menekan Biaya Produksi Beternak Lele - Suwarto Suwarto (PRIMA: Journal of Community Empowering and Services, 2017)
This IbM program in collaboration with two partners, namely: (1) Traders and Chicken butcher 'Narti Ayam, and (2) Catfish Livestock "Berlian Catfish". Partner (1) is located in Karangrejo, Ngringo village, Jaten, Karanganyar, with a distance of about 3 km from Faculty of Agriculture UNS. Business field developed by partners (1) is the business of slaughtering chicken pieces. Partners (2) located in the hamlet of Gunung Sari, Ngringo village, district. Cork, Kab. Karanganyar, Central Java with a distance of about ± 3.5 km. Business fields developed by partners (2) are catfish farms. The location is very close to both partners, only about 0.5 km. Consumer demand for chicken and catfish in Karanganyar and surrounding per day is very high, has not been able to be met by both the business partners. 1 business partners in the activities of this IbM facing major problems, namely the handling of waste chicken feathers with an average production capacity of ± 300 head / day. Very high production speeds also produce very high feather waste, which is about 100 kg of waste per day (3 tons per month). This has the potential to pollute the environment in the form of a pungent odor and pollutant source for the water body. While the two business partners in the activities of this IbM facing major problems that must provide catfish feed cost of purchasing very high, reaching an average of Rp. 1.23 million to Rp. 1,640,000 / week.IbM activity is trying to overcome the problems faced by business partners (1), by exploiting the potential of waste chicken feathers for the manufacture of catfish feed through manufacture pellets mixed with other materials that have a high nutritional value and seek to overcome the problems faced by business partners (2) , by utilizing waste chicken feathers are made of pellets can reduce the production cost of raising catfish. The application of the proposed technology will produce an integrated business activities slaughter broilers - catfish farms without waste, making it environmentally friendly, and produce coherence between slaughter chicken and catfish breeding mutually beneficial.The results that have been achieved in service activities are: (1) assistance pellet making machine 1 unit with a capacity of 40 kg / h; (2) support a high-pressure cooker (pressure cooker) 1 unit with a capacity of 70 kg; (3) assistance Removers Tools quill 1 unit; (4) Utilization of quail droppings, feathers and waste; (5) The practice of making pellets using quail dung mixed salted fish waste, and waste feathers. Help set of machine tools for the manufacture of catfish feed from raw materials to finished pellets help solve waste chicken feathers Chicken slaughtering Traders 'Narti Chicken' and can overcome the high cost of production in the Ranch Lele 'Diamond Catfish'.